Defending the nation: civic engagement for the young generation - Adhari, Nursanda Rizki; Ihsan, Ihsan; Nur Rahman, Ikman; Tesa Gumilar, Agus (Universitas Tanjungpura, 2025)
The role of two youth organizations, the Ansor Youth Movement and Muhammadiyah Youth, in implementing national defense and strengthening civic engagement amidst contemporary sociocultural challenges. The urgency of revitalizing national defense is no longer limited to the militarism dimension, but the role of the younger generation in implementing social integration by engaging with the community in the context of national defense. This research uses a descriptive qualitative approach with a case study method in Banten Province. Data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed using data reduction techniques, thematic categorization, and interpretation of meaning. The research findings show that the implementation of youth organizations is realized in cadre education, public advocacy, leadership training based on national values. The intended involvement is to make the local government a partner in implementing national defense activities, then in the engagement approach, the two organizations implement ideology, cadre development, advocacy, economic independence, literacy studies, and go to the community in need. In this implementation, social capital development emerged through the approach developed by the organization. This article recommends strengthening the synergy between youth organizations, government, and educational institutions in building an inclusive, critical, and value-oriented citizenship model